Gleissberg Cycle Dependence of Inner Zone Proton Flux - Emily J. Bregou; Mary K. Hudson; Brian T. Kress; Murong Qin; Richard S. Selesnick (Space Weather)
Abstract Inner zone proton flux from 1980 to mid‐2021 is examined using NOAA POES satellite data, indicating a long‐term increase corresponding to a one hundred year minimum in solar activity consistent with the Centennial Gleissberg Cycle. Variation of inner belt protons is correlated with decreasing F10.7 maxima over the 40‐year period, serving as proxy for solar EUV input to Earth's atmosphere. Extending an earlier study (Qin et al., 2014; https://doi.org/10.1002/2014JA020300) of >70 MeV protons from 1980 – 2021 using the South Atlantic Anomaly (SAA) peak flux, and at fixed L = 1.3, a comparison is made between the >35, >70 and >140 MeV energy channels on POES. All three energies show an increase in proton flux over the period 1998 – 2021 using a single spacecraft. The observed flux increase is correlated with decreasing F10.7 over the longer 40‐year time interval, as with the ∼11‐year solar cycle. A phase lag during Solar Cycle 24 (January 2010 – June 2021) between the F10.7 minimum and proton flux maximum was determined to be ∼500 days, the same at all energies studied. A model calculation of the inner zone proton flux is found to generally confirm the long‐term trend examined both in absolute magnitude and phase lag. It is concluded that this long‐term trend is a manifestation of the concurrent Gleissberg cycle minimum and accompanying decrease in solar EUV. Reduced EUV at solar maximum (F10.7 proxy) reduces proton loss to the atmosphere following solar maximum, thus explaining the long‐term flux increase observed.